Javanese Class Harmony : Inclusive Strategies for Special Needs Students - Nurzanah, Messi; Benedicta A., Esti Sudi Utami (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to explore the classroom management strategies used by Javanese teachers in teaching children with special needs at Tegal Regency Junior High Schools support inclusive learning. The research used was qualitative approach, through direct classroom observations and interviews with Javanese language teachers who have experience teaching students with special needs. Data analysis used interactive analysis and to test the validity of the data uses triangulation of data sources. The findings showed that Javanese teachers had developed flexible strategies according to the needs of each child with special needs. Students in the deaf-speech category would be treated differently, especially for learning that requires speaking and reading skills, such as tembang and pacelathon. Students in the slow learner category will be required to be more patient to understand the material, supported by the use of interactive learning media and by being given practice questions according to their capacity, whereas for the physically disabled category, there is no special treatment regarding learning material. Thus, the conclusion of this research highlights the important role of Javanese language teachers in Tegal Regency junior high schools in supporting the learning of children with special needs. Through a flexible approach, attention to student involvement, and collaboration between friends in the class, have succeeded in creating an inclusive and empowering learning environment, where every student has the same opportunity to grow and develop optimally in understanding and using the Javanese language.